Inclusive Education of Children With Intellectual Disabilities in the Context of Ensuring Their Right for Quality Education - Lukaniova, Liudmyla (My University, 2025)
Education is a factor that determines the success of any person in society and the national vector of development in general. It is extremely important to create a new educational space, which includes inclusive education. In modern conditions, there is a constant search for innovative ways to organise the education of children with developmental disabilities.
Keywords: inclusive education; intellectual disability; speech disorder